The Influence of Cooperative Learning Model Types of Make a Match and Learning Motivation on Indonesian Learning Outcomes Ibtidaiyah Madrasah Students in Duren Sawit - Ifa Fachriyah; Happy Karlina Marjo; Lidwina Sri Ardiasih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine whether there is an effect of the cooperative learning model type make a match and learning motivation on the learning outcomes of Indonesian students at Madrasah Ibtidaiyah in Duren Sawit. This research was conducted for three months from October to December 2019. The data analysis methods used were descriptive percentage analysis and inferential analysis. The population of this study were students of class 1 MI Al Wathoniyah 1A Duren Sawit, East Jakarta totaling 70 students. The sample in this study was 60 students who used proportional random sampling. The results showed that learning Indonesian early reading material with the cooperative method of make a match type could affect student learning outcomes. Learning motivation also affects student learning outcomes which are quite good in every action so that student learning outcomes increase. In the treatment class, there were 25 students who completed the minimum completeness criteria (KKM), 89.1%, which was classified as high and experienced an increase. Meanwhile, in the control class, students who achieved the minimum completeness criteria (KKM) were 20 students 9.9%, which was low and experienced a slight increase. Thus, the use of a make a match type of cooperative model and learning motivation greatly affects student learning outcomes in the initial reading material for Indonesian lessons in grade 1 Madrasah Ibtidaiyah Al Wathoniyah 1A Duren Sawit, East Jakarta.